2022
DOI: 10.1108/nfs-07-2022-0228
|View full text |Cite
|
Sign up to set email alerts
|

Sports nutrition knowledge translates to enhanced athletic performance: a cross-sectional study among Lebanese university athletes

Abstract: Purpose Adequate nutrition knowledge forms the foundation for optimal physical health and performance. In Lebanon, there are limited studies on the effect of nutrition knowledge on the athletes’ performance. This study aims to evaluate university athletes’ nutrition knowledge status and to identify the factors predicting athletes’ performance. Design/methodology/approach A cross-sectional survey was conducted among 384 university student-athletes, using a validated tool with modifications (Furber et al., 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Limited access to nutritious food due to financial constraints, inadequate healthcare access, and poor sanitation and hygiene conditions in low-income areas contribute to these challenges. Additionally, limited education and awareness about proper nutrition and childcare practices, economic instability leading to food insecurity, and the psychosocial stress experienced by lower-income families further exacerbate the issue (Koletzko and Toschke, 2010; Serhan et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Limited access to nutritious food due to financial constraints, inadequate healthcare access, and poor sanitation and hygiene conditions in low-income areas contribute to these challenges. Additionally, limited education and awareness about proper nutrition and childcare practices, economic instability leading to food insecurity, and the psychosocial stress experienced by lower-income families further exacerbate the issue (Koletzko and Toschke, 2010; Serhan et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Ali et al [ 40 ] highlighted disparities between male (fair knowledge, 57%) and female (poor knowledge, 49%) university student-athletes in Pakistan. Serhan et al [ 41 ] noted inadequate nutrition knowledge (mean < 75%) among university athletes in Lebanon. Bakhtiar et al [ 23 ] revealed 57.3% satisfactory nutrition knowledge among adolescent trainee athletes in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing recognition of nutrition’s multifaceted influence on both health and athletic performance has fueled a surge in research within the domain of sports nutrition ( Valenzuela, 2023 ). This growing awareness is evident in the plethora of recent research into various aspects of nutritional practices and their impact on athletic outcomes in the relevant literature ( Nobari, Cholewa & Suzuki, 2023 ; Ferrada-Contreras et al, 2023 ; Serhan, Yakan & Serhan, 2023 ; Hernández-Lougedo et al, 2023 ; Cannataro, Straface & Cione, 2022 ; Tirla et al, 2022 ; Laudisio et al, 2022 ; Miyamoto, Hanatani & Shibuya, 2021 ; Reuter & Forster, 2021 ; Bentley et al, 2021 ; Miyamoto, Hanatani & Shibuya, 2020 ; Massarani et al, 2019 ; Astley, Souza & Polito, 2017 ; Close et al, 2016 ; Knapik et al, 2016 ; Tawfik, El Koofy & Moawad, 2016 ; Reed et al, 2014 ; Halson, 2014 ; Logi Kristjánsson, Dóra Sigfúsdóttir & Allegrante, 2010 ). However, a critical review of this extensive body of literature reveals that there is limited research specifically examining the interplay between attitudes towards healthy nutrition and mental toughness.…”
Section: Introductionmentioning
confidence: 99%